Influence of oxygen on densification kinetics of WC nanopowders during SPS - Lantsev, Eugeniy; Malekhonova, Nataliya; Nokhrin, Aleksey; Chuvil'deev, Valdimir; Boldin, Maksim; Blagoveshchenskiy, Yuriy; Andreev, Pavel; Smetanina, Kseniya; Isaeva, Nataliya; Shotin, Sergey (Ceramics international, 2021)
The shrinkage of the WC nanopowders with increased oxygen content during Spark Plasma Sintering (SPS) was shown to be limited by the grain boundary diffusion with abnormally low activation energy. It was found that the reduction of the SPS activation energy may originate from the effect of oxygen on the diffusion permeability of the grain boundaries in tungsten carbide at the intensive compaction stage as well as from an abnormal grain growth at the high-temperature sintering stage. The kinetics of SPS of the WC-W2C–WO3–W nanopowders at the intense compaction stage is controlled by the sintering rate of the oxide particles with simultaneous transformation of these ones into the W2C particles and then, at the high-temperature sintering stage – by the plastic flow of the W2C particles in the presence of tungsten ones. The ceramic specimens with high density (98–99%) and ultrafine grained structure (mean grain size < 0.3 μm) having an increased hardness Hv = 30.5 GPa at minimum Palmquist fracture toughness ~ 6.5 MPa m1/2 were obtained by SPS.